Role of Emotionally Intelligence Leader in an Organisation: with special Reference to MSME Industries of Chhattisgarh - Pandey, Shrawan; Pandey, Rachana; Chandra, Ashok K (International Journal of Computer Sciences and Engineering, 2025)
The concept of Emotional Intelligence has gained significant consideration from academia, different organizations and main stream society. The concept of Emotional Intelligence with different construct conceptualized different models of Emotional Intelligence, with different corresponding measurement tools and has proposed various strategies for developing EI. Such scholarly work has made major contribution in the development of Emotional Intelligence but it has also given rise to a number of controversial aspects over which debates exist among different scholars and researchers. Therefore by looking at the existing controversies on Emotional Intelligence among the different scholars, thorough research is required in order to a bridge the gap and provide a single platform for achieving theoretical harmony in Emotional Intelligence and to effectively analyze the impacts of EI at workplace on leadership and teamwork level. The aim of the present paper is to explore the relationship between emotional intelligence and effective leadership to evaluate the tendency of emotional control of the working class both male and female at a managerial level. It revealed that emotional intelligence has great relationship with leadership styles and it combines with leadership skill which has been found statistically significant. A person with high age and high experience has better leadership skills. There is no impact of other two factors i.e. level of education and gender (male and female).